Reputation Capital of Directorships and Demand for Audit Quality - Fredriksson Antti; Kiran Anila; Niemi Lasse (Taylor & Francis, 2022)
This study examines whether boards of directors use external auditing to protect their reputation capital. We hypothesize and find that audit quality increases with the level of directors’ reputation capital. More specifically, using ten-year panel data on Finnish listed companies, we find that our measures of reputation capital based on the number of directorships that directors possess and their compensation are positively associated with various proxies for audit quality. We also find that the observed reputation effect on audit fees is stronger in companies with an audit committee, and that reputation capital matters in auditor choice in those companies in particular. In combination, our results add to the literature on the reputation capital of those in charge of corporate governance.